Forms of Greeting by Supporting Characters in Mark Twain's Novel: The Prince and The Pauper - B, Lumoindong (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
Starting a conversation by using greeting forms was considered polite when two people met. Greeting was very significant and cannot be avoided in a conversation situation. Conversation that begun with a greeting can produce good conversation construction at the next stage. One language will differ from another one in expressing its forms of greeting which, of course, were influenced by different conditions and societal backgrounds. This research was aimed at identifying, analyzing, and describing the forms and uses of greetings by the supporting characters in the novel entitled The Prince and the Pauper written by Mark Twain. The qualitative descriptive method was chosen in carrying out the research to explain in detail the results of the analysis of the research subjects’ utterances. The primary data for this research were the forms of greeting aroused from the conversation situations between the supporting characters in this novel. The data that have been obtained were then reduced, displayed and analyzed by referring to various backgrounds of the conversations that occurred, e.g.: situation, social status, position, and identity of the characters by paying attention to the concept of greeting that was proposed by Susan M. Ervin-Tripp. The results of this research showed that the forms of greeting used by the supporting characters in this novel matched or complied with the concept of greeting explained by Susan M. Ervin-Tripp.